Intake of total cruciferous vegetable and its contents of glucosinolates and isothiocyanates, glutathione S-transferases polymorphisms and breast cancer risk: a case–control study in China. Issue 6 (20th April 2020) - Zhang, Nai-Qi; Mo, Xiong-Fei; Lin, Fang-Yu; Zhan, Xiao-Xia; Feng, Xiao-Li; Zhang, Xin; Luo, Hong; Zhang, Cai-Xia
Abstract: Cruciferous vegetables contain high levels of glucosinolates (GSL) and isothiocyanates (ITC). ITC are known to induce glutathione S -transferases (GST) and thus exert their anticarcinogenic effects. This study explored the combined effects of cruciferous vegetable, GSL and ITC intake and GST polymorphisms on breast cancer risk. A total of 737 breast cancer cases and 756 controls were recruited into this case–control study. OR and 95 % CI were assessed by multivariable logistic regression. Higher cruciferous vegetable, GSL and ITC intakes were inversely associated with breast cancer risk, with adjusted OR of 0·48 (95 % CI 0·35, 0·65), 0·54 (95 % CI 0·40, 0·74) and 0·62 (95 % CI 0·45, 0·84), respectively. Compared with women carrying the GSTP1 rs1695 wild AA genotype and high cruciferous vegetable, GSL or ITC intake, carriers of the AA genotype with low cruciferous vegetable, GSL and ITC intake had greater risk of breast cancer, with adjusted OR of 1·43 (95 % CI 1·01, 1·87), 1·34 (95 % CI 1·02, 1·75) and 1·37 (95 % CI 1·05, 1·80), respectively. Persons with the GSTM1 -null genotype and lower intake of cruciferous vegetables, GSL and ITC had higher risk of breast cancer than those with the GSTM1 -present genotype and higher intake, with OR of 1·42 (95 % CI 1·04, 1·95), 1·43 (95 % CI 1·05, 1·96) and 1·45 (95 % CI 1·06, 1·98), respectively. Among women possessing the GSTT1 -present genotype, low intake of cruciferous vegetables, GSL or ITC was associated with higher risk of breast cancer. But these interactions were non-significant. This study indicated that there were no significant interactions between cruciferous vegetable, GSL or ITC intake and GST polymorphisms on breast cancer risk.